2018
DOI: 10.1111/jicd.12346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral health education in Myanmar preschool children and guardians

Abstract: Comprehensive oral health education was shown to improve guardians' knowledge of oral hygiene, and oral health habits and status of their children. It is necessary to adopt a comprehensive oral health-promotion program involving oral health-care professionals, parents, and teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In another study conducted to evaluate the effectiveness of oral and dental health preventive education given to preschool children, it was reported that children's correct toothbrushing skills improved, and plaque amounts decreased (Zeeberg, Puello, Batista, & de Sousa, 2018). In still another study conducted with preschool children, it was observed that plaque levels decreased according to the debris score index of the children after the education (Thwin, Zaitsu, Ueno, & Kawaguchi, 2018). This result of the study is consistent with the literature (Nguanjairak, Duangsong, Patcharanuchat, Muangsom, & Bradshaw, 2016;Petersen et al, 2015;Raj, Goel, Sharma, & Goel, 2013) and shows the effectiveness of the entertaining education provided.…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted to evaluate the effectiveness of oral and dental health preventive education given to preschool children, it was reported that children's correct toothbrushing skills improved, and plaque amounts decreased (Zeeberg, Puello, Batista, & de Sousa, 2018). In still another study conducted with preschool children, it was observed that plaque levels decreased according to the debris score index of the children after the education (Thwin, Zaitsu, Ueno, & Kawaguchi, 2018). This result of the study is consistent with the literature (Nguanjairak, Duangsong, Patcharanuchat, Muangsom, & Bradshaw, 2016;Petersen et al, 2015;Raj, Goel, Sharma, & Goel, 2013) and shows the effectiveness of the entertaining education provided.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the results indicated that epidemics changed people’s attitudes towards oral health prophylaxis in children and they preferred to focus on the prophylaxis. Therefore, we should develop more oral health education and promotion programs providing instruction in effective prevention and the improvement of oral health [ 14 , 15 ]. When the dental services are unavailable, dental professional staff can use ‘social’ digital platforms to instruct positive oral health behavioral.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, what parents do to influence their child’s oral health behaviours will determine their child’s future oral health [ 22 ]. At the same time, innovative school-based oral health education programmes especially designed for preschool children which incorporates parental and teachers’ involvement are essential to improve oral health behaviours and oral health status of preschool children [ 23 , 24 ]. In this study, we have developed the SIMSP to incorporate DTs, teachers, and parents in children’s oral health with the view to improve the current POHP and children’s oral health in the long term.…”
Section: Discussionmentioning
confidence: 99%